2021
DOI: 10.1155/2021/6612720
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and Environmental Impacts of Charcoal Production Activities of Rural Households in Mecha District, Ethiopia

Abstract: Ethiopia is one of the largest charcoal-producing countries in Africa where its urban consumers burn over 3 million tons per year. The purpose of this study was to measure the amount of charcoal produced and its related environmental and socioeconomic impact in the study area. A total of 305 respondents were selected by using a simple random sampling technique. The amount of greenhouse gas emissions from charcoal production was analyzed based on the Intergovernmental Panel on climate change quantification tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…Te majority (82.65%) of charcoal producers are farmers, followed by civil servants (10.2%) (Table 2; Supplementary table 2). Tis result is consistent with that of [6] in Mecha District (Ethiopia), where they reported that most charcoal producer farmers' primary occupation was charcoal production following farming activity. Tis is described by the high contribution of charcoal to household cash income and supports the declaration by Angelsen et al [1] that forest income contributes more to regular household income than is otherwise known.…”
Section: Socioeconomic and Demographic Characteristics Ofsupporting
confidence: 87%
See 4 more Smart Citations
“…Te majority (82.65%) of charcoal producers are farmers, followed by civil servants (10.2%) (Table 2; Supplementary table 2). Tis result is consistent with that of [6] in Mecha District (Ethiopia), where they reported that most charcoal producer farmers' primary occupation was charcoal production following farming activity. Tis is described by the high contribution of charcoal to household cash income and supports the declaration by Angelsen et al [1] that forest income contributes more to regular household income than is otherwise known.…”
Section: Socioeconomic and Demographic Characteristics Ofsupporting
confidence: 87%
“…Te chi-square test of independence showed that there was a signifcant association between gender and forest degradation (χ 2 � 13.225) at a 5% (P < 0.05) level of signifcance. In most of the charcoal producers (54.08%), the age ranged from 20 to 43 years, [6,8,38,39] in Narok County, Niger State, Oyo State, and Mecha District, respectively. Te chi-square test of independence showed that there was no signifcant association between age and forest degradation (χ 2 � 3.234) at the P > 0.1 signifcance level.…”
Section: Socioeconomic and Demographic Characteristics Ofmentioning
confidence: 99%
See 3 more Smart Citations